Pengembangan Media Pembelajaran Berbasis Augmented Reality (AR) pada Mata Pelajaran IPAS Kelas VIII SMP - Salmanura, Fadhila; Hendri, Nofri (Lembaga Yasin AlSys, 2024)
Augmented Reality (AR) learning media is a new learning innovation that displays interesting 3D animation visuals and makes complex and abstract concepts more real so that it triggers students' interest and curiosity in learning, so it can be used as an alternative in learning problems. This study aims to develop learning media for IPAS Class VIII Junior High School in order to produce valid media that is practical and effective for use by teachers and students This type of research is a development research (Reseacrh an Development) with the 4D (Four-D) development model. The average score for media validity assessment using Likert scale percentage presentation with media assessment by validator I is 4.93 and the percentage of 98% is categorized as